Factorial validity and norms of the German and British-English online Conflict Monitoring Questionnaire - Anja Leue (Cogent Psychology)
This study investigates individual differences of conflict monitoring as a personality trait in checking or adaption modes if information is incompatible or unexpected. In every-day life, individual differences of monitoring comprise stimulus comparison, stimulus evaluation and preparation of adjusted behavior or decisions under uncertainty of consequences. By integrating principles of facet theory and predictions on two neurobiological accounts study aims for the online Conflict Monitoring Questionnaire (CMQ) were four-fold: (1) Psychometric properties of the online CMQ are presented in a German and a British sample. (2) Cross-cultural factorial validity of the online CMQ, (3) results of measurement equivalence and (4) norms for the online CMQ are reported. In a sample of N = 890 participants comprising n = 447 German and n = 443 British participants, (1) part-whole corrected item-total correlations comprised a corresponding subset of 37 items in both samples. (2) Superior model fit was observed in a confirmatory factor analysis for a bifactor model compared to a four-factor primary-order model. (3) A Multiple-Indicator-Multiple-Cause (MIMIC) model suggested measurement variance for gender, language and age groups depending on the latent factors of the CMQ-37, but also evidence of measurement invariance. (4) Stanine and T norms are reported for the whole sample as well as for language groups and gender. The present psychometric data illustrate that self-reported individual differences of conflict monitoring differ across language groups. Thus, the personality differences of the CMQ-37 scales are described in terms of emic (i.e. culture-specific) and etic (i.e. culture-generalizing) effects.